PENERAPAN PENGGUNAAN MEDIA POHON AKSARA DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DI KELAS 1 SISWA SD NEGERI 1 NGINGIT - Octavia, Nurul; Chrisyarani, Denna Delawanti; Setiawan, Dwi Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was prompted by the low initial reading skills of first-grade students at SDN 1 Ngingit due to conventional teaching methods. The study aims to enhance these skills through the "Pohon Aksara" (Alphabet Tree) media using a Classroom Action Research (CAR) design by Kemmis & McTaggart. The subjects consisted of 28 students during the odd semester of the 2025/2026 academic year. Data were collected through reading tests, observations, and documentation, then analyzed using descriptive quantitative and qualitative methods. The results showed a significant improvement: in the pre-cycle stage, only 21.43% of students were fluent readers; this increased to 42.86% in Cycle I and reached 82.14% in Cycle II. This success was driven by the use of varied visual media, an interactive approach, and individual mentoring, which boosted student enthusiasm and confidence. It is concluded that the "Pohon Aksara" media is effective and highly recommended as an innovative solution to strengthen early literacy in lower-grade elementary school classrooms.